Multicellular Crosstalk Between Exosomes and the Neurovascular Unit After Cerebral Ischemia. Therapeutic Implications - Zagrean, Ana-Maria; Hermann, Dirk M.; Opris, Ioan; Zagrean, Leon; Popa-Wagner, Aurel (Frontiers in Neuroscience, 2018)
Restorative strategies after stroke are focused on the remodeling of cerebral endothelial cells and brain parenchymal cells. The latter, i.e., neurons, neural precursor cells and glial cells, synergistically interact with endothelial cells in the ischemic brain, providing a neurovascular unit remodeling that can be used as target for stroke therapies. Intercellular communication and signaling within the neurovascular unit, the multicellular brain-vessel-blood interface, including its highly selective blood-brain barrier, are fundamental to the central nervous system homeostasis and function. Emerging research designates cell-derived extracellular vesicles and especially the nano-sized exosomes, as a complex mean of cell-to-cell communication, with potential use for clinical applications. Through their richness in active molecules and biological information (e.g., proteins, lipids, genetic material), exosomes contribute to intercellular signaling, a condition particularly required in the central nervous system. Cerebral endothelial cells, perivascular astrocytes, pericytes, microglia and neurons, all part of the neurovascular unit, have been shown to release and uptake exosomes. Also, exosomes cross the blood-brain and blood-cerebrospinal fluid barriers, allowing communication between periphery and brain, in normal and disease conditions. As such exosomes might be a powerful diagnostic tool and a promising therapeutic shuttle of natural nanoparticles, but also a means of disease spreading (e.g. immune system modulation, pro-inflammatory action, propagation of neurodegenerative factors). This review highlights the importance of exosomes in mediating the intercellular crosstalk within the neurovascular unit and reveals the restorative therapeutic potential of exosomes harvested from multipotent mesenchymal stem cells in ischemic stroke, a frequent neurologic condition lacking an efficient therapy.